ALIH KODE DAN CAMPUR KODE PADA DIALOG ANTARTOKOH FILM BUMI MANUSIA KARYA HANUNG BRAMANTYO - Mila Amalia; Tati Sri Uswati; Udin Kamiluddin (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2023)
This study aims to describe the forms of code-switching and code-mixing as well as the causal factors found in the film Earth of Mankind by Hanung Bramantyo. This research is a qualitative descriptive study using a sociolinguistic approach. The data collection technique used in this study is the observing and noting technique. The subject of this study is the film Bumi Manusia by Hanung Bramantyo. Based on the research that has been done, there are forms of code switching and code mixing as well as the causative factors that occur in the dialogue between the characters in the film Bumi Manusia by Hanung Bramantyo. The results of this study obtained 49 data, namely 11 code switching data and 38 code mixing data. In this case, there are several languages used, including Indonesian, English, Dutch, French and Javanese.